Efficacy of Progressive Muscle Relaxation in Reducing Psychological Distress and Improving Quality of Life Among Nursing Students: A Feasibility Trial from Pakistan - Ahmed , Shakeel; Mustafa, Nazia; Aftab, Abid; Rashid Khan, Sophia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the level of psychological distress and evaluate the efficacy of Progressive Muscle Relaxation on psychological distress (stress, depression, anxiety) and quality of life among nursing students.Study Design: Mixed-methods Study.Place and Duration of Study: College of Nursing, Armed Forces Post Graduate Medical Institute, Rawalpindi Pakistan, from Jun to Aug 2024.Methodology: Phase I of the study includes the assessment of psychological distress, in which a total of 28 nursing students reported significant psychological distress based on the Depression Anxiety Stress Scale (DASS-21) and participated in testing the efficacy of PMR intervention. In phase II, a single session of PMR was used along with pre- and post-testing for study variables through DASS21, the World Health Organization Quality of Life Scale (WHOQOL-BREF), and a Demographic Information sheet (DIS) in a group setting.Result: We present initial evidence of the intervention's fidelity, with good inter-rater reliability (r=0.80), high acceptability through qualitative feedback analysis, and the feasibility of running a randomized controlled trial. Further, results revealed that after the intervention, depression scores significantly reduced with a moderate effect size (Cohen’s d=0.314). Qualitative assessment from acceptability feedback interviews complemented the findings.Conclusions: We support using PMR intervention to manage psychological distress and enhance the quality of life among nursing students in Pakistan.